Sistem Pemeliharaan Preventif Pada Peralatan Utama Stasiun Batching Plant Menggunakan Metode FMEA di PT. Azwa Utama Gorontalo - Andika, Dimas Krisna; Junus, Stella; Larossa, Esta (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The demand for high-quality concrete as a primary material in various construction projects makes the existence and optimal performance of concrete production facilities, namely batching plants, very crucial. The efficiency and operational reliability of batching plants directly impact the quality of concrete, project schedules, and production costs. Disruptions in any component, no matter how small, can result in significant downtime and economic losses. Therefore, proper and planned maintenance becomes an essential foundation for maintaining the optimal performance of batching plants. This research aims to provide practical recommendations regarding the optimal type of maintenance, in order to enhance the efficiency, reliability, and lifespan of batching plant equipment. The results show that the number of failures and total downtime for the conveyor machine amounted to 11 failures with a total downtime of 92 hours, and for the mixer, there were 9 failures with a total downtime of 85 hours and for the silo 6 times with a total downtime of 40 hours.